Biochemical metabolic enhancement acting as a dominant driver in intra-leaf CO2 diffusional response to soil nitrogen supplying in Soybean - Qihui Zuo; Siyu Tan; Lina Gao; Xueer Wang; Jian Zhang; Fenwu Liu; Kai Zhu (PLoS ONE, 2026)
Biochemical metabolism and anatomical structure within leaf tissues have been proposed as the two principal mechanisms underpinning the rapid responsiveness of mesophyll conductance ( g m ) to environmental perturbations; nevertheless, empirical evidence distinguishing which of these factors acts as the dominant driver remains scarce. The response of intra-leaf CO 2 diffusion conductance including g m and stomatal conductance ( g sc ) to soil nitrogen (N) change in soybean was systematically quantified in leaf biochemical and structural characteristics. Our data revealed that (i) soil N made a positive effect on intra-leaf CO 2 diffusion and carbon assimilation that g m and A n (net photosynthetic rate) exhibited a significant positive response to increasing N supplying from 7.5 to 15.0 g urea m -2 while g sc showed no significant N-dependence. (ii) The enhanced intra-leaf CO 2 diffusion capacity induced by N application was principally attributable to the increase in g m .(iii) The enhancement of biochemical metabolism rather than the modifications in the leaf anatomical structure constituted the predominant mechanism by which N supplementation facilitated CO 2 diffusion and carbon assimilation in soybean. (iv)Furthermore, the improvement in water use efficiency (WUE) appeared to be more closely linked to aquaporin-mediated water relations, as supported by subsequent correlation analyses.These findings will advance our understanding of the key drivers that shape g m responsiveness to abrupt environmental variations.